ACTIVATED CARBON FROM DURIAN SEED BY H3PO4 ACTIVATION: PREPARATION AND PORE STRUCTURE CHARACTERIZATION - Amri Ismail; Hanggara Sudrajat; Desi Jumbianti (Universitas Gadjah Mada, 2010)
Activated carbons have been produced from the natural biomaterial durian (Durio zibethinus) seed, using phosphoric acid (H3PO4) as the activating agent. The effects of impregnation ratio, activation temperature, heating rate on the carbon surface area, porosity and mass yield are presented. A two step process has been used, the first step was a low temperature impregnation at 150 °C using phosphoric acid and the second step was the carbonization at high temperatures, namely, 600 and 900 °C. The most outstanding carbon with the highest surface area of 2123 m2/g was prepared using an impregnation ratio of 2, an activation temperature of 600 °C for 4 h and a heating rate of 1 °C/min.